Microbial and physical evaluation of selected cough syrups sold at peripheral drug outlets in Bushenyi District, South Western Uganda - Matovu, Johnmary; Gonahasa, Mark; Munanura, Edson Ireeta; Ntulume, Ibrahim; Tusiimire, Jonans (African Journal of Pharmacy and Pharmacology, 2023)
Syrups, being non-sterile liquid pharmaceutical formulations, are prone to microbial contamination. The most common microbial contaminants are bacteria and fungi. Contamination of oral liquid pharmaceuticals makes them hazardous due to potential to cause infections, and may also change their physical, chemical, and organoleptic properties. This study assessed the microbial quality and physical characteristic parameters of 10 samples from each of four different brands of cough syrup sold in Ishaka, Bushenyi district. Microbial quality was assessed on samples of the syrups using spread-plate method via surface spreading of prepared dilutions of the different samples on agar plates. Plates were then incubated and colonies counted and expressed as number of colony forming units per milliliter (CFU/ml). The brand mean pH ranged from 3.04 to 5.02 and density from 1.05 to 1.35 g/cm3 respectively. All sampled brands were compliant for pH, density, color and taste specifications. Out of the 40 tested samples, 57.5% showed total viable counts within the acceptable British Pharmacopoeia (BP) limit (≤100 CFU/ml), while 42.5% showed results outside the specified limit. All samples complied with BP requirements for Staphylococcus aureus while 97.5% samples complied with BP requirements for Escherichia coli. Based on mean CFU/ml, all the four brands met the acceptance limits for both S. aureus and E. coli, but one of the brands had an unacceptably high total viable count. Adequate quality control measures and stringent regulatory monitoring should be enforced in the supply chain to reduce on chances of product contamination.
Keywords: Cough syrups; Pharmaceutical quality; Microbial contamination; Community pharmacy; Bushenyi